EFFECT OF TILLAGE AND NITROGEN LEVELS ON GROWTH AND YIELD - Singh, GURMINDER; Kumar, RAKESH; Kumar, SATINDER (Annals of Agricultural Research, 2014)
Experiment was designed in split plot with four replications, three levels of tillage i.e. zero tillage (by using no-till drill), minimum tillage (one ploughing followed by one planking), minimum tillage (one ploughing followed by one planking) and conventional tillage were taken in main plot treatments. Whereas, five nitrogen levels (0, 80, 100, 120 and 140kg/ha) were taken as sub-plots treatments. Various growth and yield attributing factors (viz.plant height, cobs per plant, cob length, grains per cob and 1000 grain weight) were observed. Data on different levels of tillage did not indicate any significant difference for growth, yield attributing characters, grain yield, stover yield and harvest index. Maximum grain yield of 39.5q/ha was recorded in conventional tillage, which was only numericaly different to other treatmetns. But the cost of cultivation was less in case of no tillage, as compared to other tillage treatmetns.